Emerging three-dimensional neuronal culture assays for neurotherapeutics drug discovery - Rathore R.S.; R Ayyannan S.; Mahto S.K. (My University, 2025)
Introduction: Development of in vitro models mimicking the physiology and pathophysiology of the brain is essential and remains a major challenge for the discovery of neurotherapeutics. Intensive research efforts over the past two decades led to the development of various two-dimensional/three-dimensional (3D) in vitro models of the central nervous system, and these models have been found to be very promising for studying the pathology of several neurological disorders and for the screening of neurotherapeutics. Areas covered: This review highlights various in vitro 3D neuronal cell culture (3DNCC) techniques that exhibit tremendous potential in the screening and development of new chemical entities for neurodegenerative disorders. Also, the advantages and challenges associated with these 3DNCC models are discussed at length. Expert opinion: Emerging microfluidics-based 3DNCC technologies and 3D bioprinting of neuronal tissues can enable medicinal chemists to reproduce brain-like tissue models at a realistic scale and also to perform site-specific in vitro mechanistic studies for evaluating neurotherapeutics. Combining optogenetics with 3DNCC may improve the noninvasive, continuous, and real-time recording of the neural network activity that is crucial for the discovery of neuropharmacological agents. Further, brain-like tissue spheroids may serve as promising tools for investigations into brain cell differentiation and neuronal degeneration. © 2022 Informa UK Limited, trading as Taylor & Francis Group.